Training on making shredded toman fish (channa micropeltes) as a featured product of Tahura Lati Petangis, Paser Regency - Evi Setiyowati; Fitriyana Fitriyana (Universitas Muhammadiyah Magelang, 2021)
The Community Service aims to empower the local potential of Paser Regency through the development and application of science and technology in the food sector. The partners are the Forest Farmers Group (KTH) and the Tahura Lati Petangis Farmer Women's Group (KWT) of Paser Regency. The main problem is that the potential of toman fish (Channa micropeltes) has not been maximized to become feature products and unique processed products of the Paser regency. The method used to achieve the objective is training and mentoring in the manufacture of shredded toman fish through tutorials and demonstrations. The result shows that the partners have understood and have entrepreneurial skills, especially shredded toman fish. At the end of the activity, the service team donated floss production equipment.